Keterampilan Teknologi Informasi Pegawai Kantor Kecamatan Colomadu - Lu’lu’ Siti Jamilah; Patni Ninghardjanti; Tutik Susilowati (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
This study aims to (1) knowing the description of employees' IT skills carried out at the Colomadu District Office, (2) knowing the efforts made in improving IT skills carried out at the Colomadu District Office, (3) knowing the things that affect the mastery of employees' IT skills. This research is a qualitative research supported by simple quantitative research with a case study. The data sources for this research include events related to difficulties in operating information technology for employees, informant (employees working at the Colomadu District Office). The sampling technique was carried out using purposive sampling technique. Data collection was carried out by interviews, observation, documentation and questionnaires. The validity test technique used is the credibility test with source triangulation and technique triangulation. transferability test, dependability test, confirmability test. Data analysis using interactive and flowing models. The results of this study are, (1) An overview of the IT skills of the employees of the Colomadu District Office, namely there are employees who only master basic IT skills, there are employees who cannot operate IT at all and there are employees who are quite proficient in IT. (2) Efforts to improve the IT skills of employees of the Colomadu District Office, namely: a) sending employees to take part in Bimtek and Training, b) providing motivation by the leadership, c) self-study. (3) factors that influence the IT skills of Colomadu District Office employees, namely: a) age factor, b) lack of self-awareness of employees, c) no special training for employees who are less skilled.